Street-Level Policy Entrepreneurs: Activating Policy Capacity in Local Food Security Implementation - Faisal Ardiansyah (Journal of Social Science and Economics (JOSSE), 2026)
This article examines how street-level actors activate policy capacity during the local implementation of Indonesia's food security policy. Existing studies usually explain weak implementation through institutional fragmentation, cross-sector coordination problems, and top-down program design. However, they say less about the micro-practices through which frontline actors keep policy working amid fragmentation. The study adopts a qualitative, embedded, multiple-case design across three districts of South Sulawesi and draws on 50 semi-structured interviews, policy and implementation documents, and limited field observations. The analysis employed theory-driven thematic analysis, combining deductive coding from the policy capacity and street-level policy entrepreneurship literatures with inductive refinement during within-case and cross-case comparisons. The findings show that implementation depends not only on formally available organizational capacity, but also on capacity activated from below by extension workers, village governments, and farmer-group facilitators. These actors re-verified beneficiary lists, reinterpreted targets, aligned village resources with district programs, and built informal coordination across agencies and communities. Under favorable local conditions, such practices moved beyond routine discretion and became street-level policy entrepreneurship. The article contributes to policy implementation studies by showing that analytical, operational, and political capacities are enacted in practice rather than merely stored in formal institutions.